Rediscovery of Premna lucidula Miq (Lamiaceae) in Mount Nglanggeran Gunungkidul - Widodo, Widodo; Luthfi, Muhammad Jafar (Proceeding International Conference on Science and Engineering, 2017)
Premna lucidula Miq (Lamiaceae) were found at S 07o 50’ 29.4”; E 110o 32’ 10.2” about 497 meter above sea levelin mount Nglanggeran, Gunungkidul, Yogyakarta. Identification was based on literature and herbarium specimen. The research was conduct using exploration method, morphological observation, and specimen collection. Premna lucidula is a shrub or small scandent tree. The specific character for its identification was inflorescence, leaf, fruit and stem structure. This paper described the important character of leaf, stem, flower, and fruit of Premna lucidula in mount Nglanggeran Gunungkidul Yogyakarta for support Backer & Bakhuizen (1965) description. Premna lucidula were recorded in Pacitan (Central Java) by Horsefied hundred years ago. The lack of subsequent report on this species was due to misidentification or ignorance of the importance of taxonomic research. Accurate description and examination of any plant species were needed for its conservation and awareness of public to local biodiversity.